PENGARUH 4P TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi Kasus di Kedai Bob’s Lounge) - Kundrat; Lily Sumarti; Ajidani Ichwanudin (Program Studi Agroteknologi Faperta UNIBBA, 2022)
Coffee is an agricultural commodity that is very popular with the people of Indonesia at this time. Many Indonesians lately spend their time just enjoying coffee in coffee shops. The increase in consumers of ready-to-eat coffee in Bandung has resulted in the opening of many coffee shops that offer various types of quality local coffee, supported by comfortable places, affordable prices and delicious coffee flavors. This study aims to determine the effect of the 4P marketing mix on the sale of coffee drinks at Kedai Kopi (Case Study at Kedai Bob's Lounge). The research location is at Jalan Captain Surwono No. 196 RT 03 RW 03 Banjaran District, Bandung Regency. The research location was chosen purposively (deliberately). The sampling method used in this study is accidental sampling method, so the sample in this study is coffee consumers who come and buy coffee to Bob's lounge and are considered suitable to be respondents, namely as many as 40 people. The data collection method was obtained from primary data and secondary data. Primary data obtained from direct interviews with consumers who come directly to the shop. Secondary data is obtained from various sources, such as journals, internet, thesis, and data from government agencies. The data analysis method used multiple linear regression analysis using SPSS version 25. The results of the study of the influence of 4P on consumer purchases of coffee at Bob's lounge coffee shop using the F test showed that the 4P variables (Product, Price, Place and Promotion) simultaneously had a positive and significant effect. on consumer purchasing decisions for coffee at Bob's Lounge coffee shop, where the value of Fcount is 3,554 > Ftable 3,06. while the most dominant variable in influencing purchases is the price variable, based on the results of the T test, the value of Tcount is 3.106> Ttable is 2.119.